OroSYN - Arzmi, Mohd Hafiz (2019)
OroSYN stands for ‘oral synbiotic’ which is a formulation for various oral healthcare products such as mouthwash and toothpaste. The oral healthcare products contain oral probiotics and prebiotics which used to maintain healthy oral cavity.